2011
DOI: 10.1007/s10930-011-9354-9
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analyses of Sirt1-Mediated Cisplatin Resistance in OSCC Cell Line

Abstract: Oral squamous cell carcinoma (OSCC) accounts for about 90% of malignant oral lesions, and is recognized as the third most common cancer in developing nations and the sixth most common cancer worldwide. While chemotherapy remains the primary treatment for both resectable and advanced OSCC, most OSCC are naturally resistant to anticancer drugs, rendering new therapeutic avenues in dire need. Sirt1, a class III histone deacetylase, was linked to cisplatin resistance in several cancer types; however, the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…In Sirt1-overexpressed OSCC cell line Tca8113, Sirt1 displayed protective function under cisplatin treatment. Proteomics showed that Anxa4 was overexpressed in pcDNA3.1-Sirt1-transfected Tca8113 cells compared with mock vector [70]. The results indicated that Sirt1 induces cisplatin resistance might via Anxa4 in OSCC.…”
Section: Anxa4 and Oral Squamous Cell Carcinomamentioning
confidence: 89%
See 2 more Smart Citations
“…In Sirt1-overexpressed OSCC cell line Tca8113, Sirt1 displayed protective function under cisplatin treatment. Proteomics showed that Anxa4 was overexpressed in pcDNA3.1-Sirt1-transfected Tca8113 cells compared with mock vector [70]. The results indicated that Sirt1 induces cisplatin resistance might via Anxa4 in OSCC.…”
Section: Anxa4 and Oral Squamous Cell Carcinomamentioning
confidence: 89%
“…Most OSCC are naturally resistant to anticancer drugs, and searching for therapeutic target of OSCC is invaluable [70]. Anxa4 is regulated by Sirt1 in OSCC.…”
Section: Anxa4 and Oral Squamous Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Oral squamous cell carcinoma (OSCC) accounts for about 90% of oral malignancies, and is the third most common cancer in developing nations and the sixth most prevalent tumor worldwide [1]. Treatment of OSCC is usually based on surgery or radiation, with or without concomitant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, overexpressed SIRT1 in leptin cells might result in a higher threshold for ROS mediated-apoptosis and explain the resistance to CDDP after leptin exposure. In fact, some works have demonstrated that SIRT1 upregulation contributes to CDDP resistance in association with altered mitochondrial metabolism [65,66]. On the other hand, previous studies from our laboratory and others demonstrated that leptinsignalling pathway induces phosphorylation of STAT3 [9], and it is widely accepted that constitutive activation of the STAT3 pathway confers resistance to CDDP-induced apoptosis in ovarian cancer cells [67,68].…”
Section: Discussionmentioning
confidence: 97%